2016
DOI: 10.1227/neu.0000000000001151
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Surgical Predictors of Complications Following Surgery for the Treatment of Cervical Spondylotic Myelopathy

Abstract: BMI, body mass indexCSM, cervical spondylotic myelopathymJOA, modified Japanese Orthopaedic AssociationOPLL, ossification of the posterior longitudinal ligament.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 35 publications
2
44
0
2
Order By: Relevance
“…Our findings may contribute to explaining why patients with a longer preoperative duration of symptoms achieve suboptimal surgical outcomes with respect to neurological recovery, functional impairment, and quality of life (7,42,43). We demonstrated that patients with a duration of symptoms greater than or equal to 6 months exhibited smaller functional improvements in functional recovery at 2 years following decompressive surgery than those with a duration of symptoms less than 6 months.…”
Section: Discussionmentioning
confidence: 56%
“…Our findings may contribute to explaining why patients with a longer preoperative duration of symptoms achieve suboptimal surgical outcomes with respect to neurological recovery, functional impairment, and quality of life (7,42,43). We demonstrated that patients with a duration of symptoms greater than or equal to 6 months exhibited smaller functional improvements in functional recovery at 2 years following decompressive surgery than those with a duration of symptoms less than 6 months.…”
Section: Discussionmentioning
confidence: 56%
“…This was done using prospectively collected data on 743 patients enrolled in either the CSM-International or the CSM-North America multicenter study. We incorporated results from our original North American prediction study and external validation study to create a clinically relevant and globally valid model that could be implemented into surgical practice 6,7 . Based on our findings, patients were more likely to achieve a score of ‡16 on the mJOA if they were younger, had milder myelopathy and a shorter duration of symptoms preoperatively, did not smoke, had fewer and less severe comorbidities, and did not present with impaired gait.…”
Section: Discussionmentioning
confidence: 99%
“…Eine Überlegenheit eines Verfahrens hinsichtlich der Besserung der Symptome der Myelopathie ließ sich nicht herausarbeiten [21]. Auch die prozentuale Komplikationsrate ist vergleichbar, wenngleich sich die Qualität der Komplikationen unterscheidet: Bei den anterioren Operationen finden sich neben der bereits erwähnten ASD vergleichsweise häufiger Heiserkeit, Dysphagie und Pseudarthrose/Implantatversagen, bei posterioren Eingriffen Wundinfektionen, Nackenschmerzen sowie eine C5-Parese [22,23].…”
Section: Operative Therapie Bei Zervikaler Spondylose: Posteriore Verunclassified